Productivity Status of Ten Year Old Silvipasture System in Red Lateritic Soil of Chhattisgarh Plains - Umrao, Rajiv; Bijalwan, Arvind; Naugraiya, M. N. (Indian Forester, 2010)
The study conducted in the silvipastoral system indicated that the collar diameter, DBH and tree height for stands of Dalbergia sissoo, Gmelina arborea, Pongamia pinnata and Terminalia arjuna were ranged from 12.01 to 15.03 cm, 9.06 to 13.1 cm and 5.40 to 7.19 m respectively. The over all dry matter production was found in order of a D.sissoo (45.18 kg tree-1) G. arborea (36.97 kg tree-1) P. pinnata (26.74 kg tree-1) and T. arjuna (23.12 kg tree -1). The under storey pasture crop of Chrysopogon fulvus > Stylosanthes hamata get established during initial growing stage of silvipasture system. As soon as the tree canopy developed the invasion of local/ native flora gets interacted with the growing species and started to influence the quality and quantity production of established pasture crops which ultimately increase the productivity of forage grasses. The study indicated that Dalbergia sissoo and Gmelina arborea species based silvipasture system was found comparatively more suitable for development and utilization of red lateritic wasteland. The systematic compatible tree-grass-legumes combination was observed better for optimum growth and biomass production as well as conservation of environment.